Implementation of The Compassion Learning in Islamic Elementary School - Shobirin, Ma’as; Rokhman, Fathur; Zulaeha, Ida; Utomo, Udi (Proceedings of International Conference on Science, Education, and Technology, 2024)
Learning compassion is an important aspect that teachers must pay attention to in instilling kindness in students. This kindness will have an impact on comfort and good relationships between teachers and students. The learning process does not only touch on the knowledge aspect, but also the behavior and involvement of students. This research aims to describe the implementation of Compassion learning at MI Miftahul Akhlaqiyah Semarang and look at the challenges that occur in implementing Compassion learning. This research is field research using a qualitative approach. The research location was at MI Miftahul Akhlaqiyah Semarang and was carried out for 3 months. Data collection techniques used were interviews, observation and document analysis. Research data analysis was carried out in the form of data reduction, data presentation and concluding. The results of this research show that the implementation of Compassion learning is going well through planning, implementation and evaluation. Some of the obstacles faced by school are the form of a complex socio-cultural context, the readiness of human resources that need to be improved, as well as the need for increased supporting facilities and infrastructure. Stakeholders also have a crucial role in ensuring the success of this program